Burden of road traffic injuries in Nepal: results of a countrywide population-based survey. (27th April 2015) - Nepal, Sarthak; Gupta, Shailvi; Wong, Evan G; Gurung, Susant; Swaroop, Mamta; Kushner, Adam L; Nwomeh, Benedict C
Abstract: Background: Road traffic injury has emerged as a leading cause of mortality, contributing to 2·1% of deaths globally and is predicted to be the third highest contributor to the global burden of mortality by 2020. This major public health problem disproportionately affects low-income and middle-income countries, where such incidents are too often underreported. Our study aims to explore the epidemiology of road traffic injurys in Nepal at a population level via a countrywide study. Methods: The Surgeons OverSeas Assessment of Surgical Need (SOSAS) tool, a cluster randomised, cross-sectional nationwide survey, was conducted in Nepal between May 25, and June 12, 2014. Two-stage cluster sampling was performed: 15 of 75 districts were chosen randomly proportional to population; within each district, after stratification for urban and rural, and three clusters were randomly chosen. Questions were structured anatomically and designed around a representative spectrum of surgical conditions. Road traffic injury-related results were reported. Findings: 1350 households and 2695 individuals were surveyed with a response rate of 97%. 75 road traffic injuries were reported in 72 individuals (2·67% [95% CI 2·10–3·35] of the study population), with a mean age of 33·2 years (SD 1·85). The most commonly affected age group was 30–44 years, with females showing significantly lower odds of sustaining a road traffic injury than men (crude odds ratio 0·29 [95% CI 0·16–0·52]). Road traffic injuries composed 19·8% of the injuries reported. Motorcycle crashes were the most common road traffic injuries (48·0%), followed by car, truck, or bus crashes (26·7%), and pedestrian or bicycle crashes (25·3%). The extremity was the most common anatomic site injured (74·7%). Of the 80 deaths reported in the previous year, 7·5% (n=6) were due to road traffic injuries. Interpretation: This study provides the epidemiology of road traffic injuries at a population-based level in the first countrywide surgical needs assessment in Nepal. WHO reported that mortality due to road traffic injuries in Nepal in 2011 was 1·7%, whereas our study reported 7·5%, consistent with the concept of underreporting of deaths in police and hospital level data noted in previous literature. Road traffic injuries continue to be a significant problem in Nepal, probably greater than previously reported; future efforts should focus on addressing this growing epidemic through preventive and mitigating strategies. Funding: The Association for Academic Surgery and Surgeons OverSeas